Blood pressure variability and brain morphology in elderly women without cardiovascular disease. (19th March 2019) - Haring, Bernhard; Liu, Jingmin; Salmoirago-Blotcher, Elena; Hayden, Kathleen M.; Sarto, Gloria; Roussouw, Jacques; Kuller, Lew H.; Rapp, Steve R.; Wassertheil-Smoller, Sylvia
Abstract : Objective: To examine the relationship between blood pressure (BP) variability (BPV), brain volumes, and cognitive functioning in postmenopausal women with few modifiable cardiovascular risk factors. Methods: Study participants consisted of postmenopausal women enrolled in the Women's Health Initiative Memory MRI study (WHIMS-MRI) without cardiovascular disease, diabetes mellitus, hypertension, or current smoking at baseline (1996–1999). BP readings were taken at baseline and each annual follow-up visit. BPV was defined as the SD associated with a participant's mean BP across visits and the SD associated with the participant's regression line with BP regressed across visits. Brain MRI scans were performed between 2004 and 2006. Cognitive functioning was assessed at baseline and annually thereafter with the Modified Mini-Mental State Examination (3MSE) scoring until 2008. The final sample consisted of 558 women (mean age 69 years, median follow-up time [interquartile range] 8 [0.8] years). Results: In adjusted models including mean systolic BP, women in the highest tertile of systolic BPV had lower hippocampal volumes and higher lesion volumes compared to women in the lowest tertile. No relationship between BPV and 3MSE scoring was detected. Conclusions: In postmenopausal women with few modifiable cardiovascular risk factors, greater visit-to-visit systolic BPV was associated with reductions in hippocampal volume and increases in lesion volumes at later life. These data add evidence to the emerging importance of BPV as a prognostic indicator even in the absence of documented cardiovascular risk factors.